2010
DOI: 10.1243/13506501jet673
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing surface texture for hydrodynamic lubricated contacts using a mass-conserving numerical approach

Abstract: Surface texturing has been shown to reduce friction and increase the film thickness in various tribological applications (hydrodynamic bearings, mechanical seals, and cylinder-liner contacts). However, only few studies discuss optimal texturing properties, and most of them focus on the optimal dimple shape. This article proposes an in-depth study on the influence of cavitation and of different texturing parameters, especially the dimple depth, the texture extent, and the dimple aspect, on the hydrodynamic perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
147
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(176 citation statements)
references
References 28 publications
14
147
0
3
Order By: Relevance
“…The optimal texture geometry (groove depth and total texture length) was found to vary significantly with the bearing convergence ratio and width-to-length ratio. Similar trends on the effects of texture patterns on bearing load capacity, a Corresponding author: chpap@central.ntua.gr accompanied by illustration of reduction in friction coefficient, were presented in the works of Cupillard et al [2] and Dobrica et al [3]. Further attempts to optimize textured bearings include the work of Van Ostayen et al [4] (maximization of bearing load capacity using a PDEconstrained optimization solver) and Buscaglia et al [5] (minimization of friction coefficient of slider bearings comprising rectangular dimples).…”
Section: Introductionsupporting
confidence: 68%
“…The optimal texture geometry (groove depth and total texture length) was found to vary significantly with the bearing convergence ratio and width-to-length ratio. Similar trends on the effects of texture patterns on bearing load capacity, a Corresponding author: chpap@central.ntua.gr accompanied by illustration of reduction in friction coefficient, were presented in the works of Cupillard et al [2] and Dobrica et al [3]. Further attempts to optimize textured bearings include the work of Van Ostayen et al [4] (maximization of bearing load capacity using a PDEconstrained optimization solver) and Buscaglia et al [5] (minimization of friction coefficient of slider bearings comprising rectangular dimples).…”
Section: Introductionsupporting
confidence: 68%
“…Moreover, www.advancedsciencenews.com www.aem-journal.com surface structures with a larger structural depth have a higher probability for cavitation, thus reducing the oil film thickness and load bearing capacity. [23,35] Taking the worsened frictional behavior of A3 into consideration, the idea was to check whether the additional laser pattern leads to an improved frictional performance.…”
Section: Friction and Wear Behaviormentioning
confidence: 99%
“…Making use of Reynolds model, Gadeschi et al [44], and later Checo et al [21] employing Elrod-Adams model, showed that for a fixed load it is possible to obtain a configuration that minimizes the friction only for moderate R/L (≈ 10) or higher. These results are in agreement with pioneering experiments made by Costa & Hutchins [31], and with latter studies by Tomanik [85,86], Kovalchenko et al [60], Yin et al [90], Scaraggi et al [81], among others [33,2,50].…”
Section: Algorithm 4: Dynamic Gauss-seidel For Reynolds Equation Withsupporting
confidence: 92%